Surgical anatomy of recurrent laryngeal nerve during thyroid and laryngeal surgeries - Pantha, Trideep; Mathur, N.N.; Bhandary, S. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Objective: To determine the anatomic relationship of recurrent laryngeal nerve with inferior thyroid artery, tracheo-oesophageal groove and Berry’s ligament and to determine the thickness and terminal branching pattern of recurrent laryngeal nerve. Material and Methods: Descriptive prospetive study was conducted in the department of Otorhinolaryngology and Head and Neck surgery in BPKIHS, Dharan, between July 2008- June 2009 including all patients undergoing thyroidectomy and total laryngectomy during the study period. Result: RLN frequently passed behind the inferior thyroid artery and occupied the tracheo-oesophageal groove in the left side than on the right. The average diameter of the nerve was 1.88 mm and the nerve commonly terminated as a single trunk. Conclusion: The nerves were commonly found deep to the ITA (96.2% on left side and 88% on right). The segment of RLN vulnerable to surgical injury between the crossing point of ITA to its entry in the larynx was found to be 3.13 cm (SD=0.29cm). The average thickness of the nerve was 1.68mm however the thickness increased as the surgery progressed and at the end of surgery. All the RLNs on the left side were found completely within the TOG while some variations were seen on the right side.